The family's role in assisting hypercholesterolemia individuals to controlling serum cholesterol level - Saryono bin Tujin Dimyati (Universiti Kebangsaan Malaysia, 2011)
High serum cholesterol level increases the risk of stroke and coronary heart diseases. Family has an important role to maintain and to reach a normal cholesterol level in the blood. The aim of this research was to explore the role of family in monitoring and maintaining serum cholesterol level among hypercholesterolemia individuals.